Burger Manjah / Nur Izzah Sa'don ... [et al.] - Sa'don, Nur Izzah; Baharudin, An Nurain Nadhirah; Cik Nordin, Nurul Aiza; Mohamad Zulkifli, Nornazifa (2021)
A company or an inventive entity engaged in commercial, industrial, or professional activity is referred to as a business. Businesses can be for-profit or non- profit enterprises dedicated to a charity mission or a social cause. In other words, business is a platform for earning profit and selling products or service that use a lot of effort and activities to be success. The Business Model Canvas is an entrepreneur's tool for imagining, designing, and reinventing their business model. Alexander Osterwalder, a Swiss business theorist and author, developed it. The purpose of this canvas is to provide insights on how customers are served, what value propositions are supplied through which channels, and how the business makes money. In addition, a business plan is used by many organizations in order to ensure that their business follows a step towards achieving its objectives. So, to make sure that our group business " BURGER MANJAH" is going down the right path. We're also developing a business modal canvas to better understand our business and what kind of target we're going to achieve.